Actividad antioxidante y factor de protección solar de cáscara de ananas comosus (l.) merrill “piña” - Salas Huayan, Andres Michel (2016)
This research aims to evaluate the antioxidant activity and sun protection factor of shells Ananas comosus (L.) Merrill cv. Smooth Cayenne and Ananas comosus (L.) Merrill cv. MDII identified in the Herbarium Truxillense (HUT), where they were assigned codes 58489 and 58490 respectively. The lyophilized cascara extracted with ethanol 96 ° G.L then concentrated and lyophilized.; obtaining the freeze-dried extract of the peel. Phenolic compounds were quantified by the Folin-Ciocalteu, and were expressed as gallic acid equivalents (EAG), whose values are 11 mg EAG / g and 12 mg EAG / g for the "white pineapple" and "yellow pineapple" respectively. The antioxidant activity was determined by the method of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and as expressed as mean inhibitory concentration (IC50) whose values obtained ranged from 0,012 ± 0,75311 mg EAG / mL for white pineapple and of 0,8091 ± 0,012 mg EAG / mL for yellow pineapple. Also, the sun protection factor for lyophilised extracts meeting with yellow Piña 1,47 and 1,35 for white pineapple was determined. The correlation between phenolic content and antioxidant activity IC50 of direct type was with lower significance level of 0.01. Concluding that the higher phenolic content of lyophilized extract of Ananas comosus (L.) Merrill, the lower the antioxidant activity due to the low quality thereof